PENGARUH MODAL MANUSIA, MODAL STRUKTURAL, MODAL RELASIONAL, TERHADAP KAPABILITAS INOVASI DAN EFISIENSI OPERASIONAL MODAL SERTA IMPLIKASINYA TERHADAP KINERJA BISNIS (Studi pada Usaha Mikro Kecil dan Menengah Kuliner di Kota Semarang) - Saddam F, Muammar; Mahfudz, Mahfudz (Diponegoro Journal of Management, 2017)
The study examines the influence of Intellectual Capital elements named Human Capital, Structural Capital, Relational Capital, and Capital Employed Efficiency to Bussiness Performance with Innovation Capability and Capital Employed Efficiency as intervening variables. There are 70â€™s owners and managers of culinary sector SMEs in Semarang City that selected to become object for this research.This study representing an empirical test wich using random sampling techniques on data collection.. The data analyze is done by using Stuctural Equation Modelling ( SEM) premises program VisualPLS (Partial Least Square).Hypothesis testing results show that of the six hypotheses that have been proposed there are five acceptable hypothesis. The accepted hypothesis are hypothesis 1 (there is significant influence between Structural Capital to Innovation Capability) hypothesis 2 (there is significant influence between Structural Capital to Business Performace), hypothesis 3 (there is significant influence between Huma Capital to Bussiness Performance), Hypothesis 4 (there is significant influence between Relational Capital to Business Performance) hypothesis 5 (there is significant influence between Innovation Capability to Business Performace).Â  Furthermore, there is one rejected hypothesis or no significant influence, the hypothesis is hypothesis 6 (there is no significant influence between Capital Employed Efficiency to Bussiness Performance).